2020
DOI: 10.3390/ijerph17155266
|View full text |Cite
|
Sign up to set email alerts
|

P300 Measures and Drive-Related Risks: A Systematic Review and Meta-Analysis

Abstract: Detecting signs for an increased level of risk during driving are critical for the effective prevention of road traffic accidents. The current study searched for literature through major databases such as PubMed, EBSCO, IEEE, and ScienceDirect. A total of 14 articles that measured P300 components in relation to driving tasks were included for a systematic review and meta-analysis. The risk factors investigated in the reviewed articles were summarized in five categories, including reduced attention, distraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…The present study also found that the P300 amplitude produced by medium risks was smaller than that of low and high risks. The amplitude accounts for the amount of attentional resources allocated to the task [ 32 ]. The P300 component is related to decision evaluation [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…The present study also found that the P300 amplitude produced by medium risks was smaller than that of low and high risks. The amplitude accounts for the amount of attentional resources allocated to the task [ 32 ]. The P300 component is related to decision evaluation [ 33 , 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[136], [137], [138], [139], [140], [141], [142], [143], [144], [145], [146], [147] present and how the P300 signal can help people interact with their surroundings more easily. These included helping them assess lights, doors, TV, etc.…”
Section: F Classification Of Articles By Application Domain/ Fieldmentioning
confidence: 99%
“…We know [ 22 , 23 , 24 ] that a much more effective method for increasing road safety is changing the stereotypes of typical behavior of road users. The analysis [ 25 , 26 ] shows that statistically significant effects of changes in people’s behavior are formed under conditions of creating an atmosphere of reward for the required behavioral imperative and, conversely, punishment in case of violations of the prescribed rules.…”
Section: Analysis Of the Issue–theoretical Foundationsmentioning
confidence: 99%